A multipronged approach to teaching end‐of‐life care to student pharmacists. Issue 4 (15th February 2021) - Howard, Meredith L.; Atanda, Adenike; Gaviola, Marian L.
Abstract: Introduction: Student pharmacists are typically taught topics regarding end‐of‐life care through required didactic courses or professional electives. Important topics such as death and dying and empathetic communication skills surrounding difficult end‐of‐life care discussions are often unaddressed. To best equip students with the skills needed for practice, it is important to expose them to multiple aspects of end‐of‐life care. Objective: To evaluate the impact of a coordinated multipronged teaching approach including a workshop‐based activity on student pharmacists' initial perceptions, knowledge, and confidence related to end‐of‐life care. Methods: Within our curriculum, topics surrounding end‐of‐life care have historically focused on pharmacotherapy with minimal time spent on conversation practice and empathy development. In spring 2019, we conducted an all‐day session incorporating various teaching approaches (ie, didactic lecture, ethical debate, Death over Dinner workshop) to prepare students to engage in these difficult discussions. A 21‐item survey, administered at three time points (pre‐, mid‐, post‐), assessed student pharmacists across three domains: Perceptions, Confidence, and Knowledge surrounding end‐of‐life. Results: Ninety‐six students participated in the session with 91% completing the pre‐survey, 69% completing the midpoint, and 59% completing the post‐survey. Forty‐nine (51%) completed matched survey responses across all time points. There was significant improvement in 13 (62%) of the survey items across three domains: 43% of items related to perception, 43% knowledge, and 100% confidence. Conclusions: A multipronged, workshop‐based approach to teaching end‐of‐life care to facilitate difficult discussions surrounding death improved perceptions, confidence, and perceived knowledge among student pharmacists. This approach provided numerous avenues for students to learn and develop empathetic communication skills surrounding end‐of‐life care and represents an innovative approach to prepare students for conversations surrounding death and dying within their professional and personal lives.